Pelatihan Sistem Pengajuan Keuangan untuk Meningkatkan Kinerja Pengurus Yayasan Dompet Yatim dan Dhuafa Depok - Dinda Mirranty Legowo; Ferdiyan Syah; Hanif Fajrin; Indah Purnamasari (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2023)
The main purpose of community service activities in the form of training on the financial submission system of the Dompet Yatim and Dhuafa Foundation is to help increase the knowledge of the Foundation's administrators in terms of using the financial submission system that has been applied to this Foundation previously. With theimplementation of this system, it is hoped that the daily operational activities of the Foundation will be more optimal where the existence of the Foundation's financial submission system will make it easier for administrators to make financial submissions anywhere and anytime according to the needs of their respective divisions. This community service activity was carried out in the form of training and guidance to the relevant Foundation administrators and was carried out for two days at the secretariat office of the Dompet Yatim Foundation and Dhuafa Depok. There are four stages in this PKM activity, namely the planning, preparation, implementation and evaluation stages. At the planning stage, surveys and interviews with relevant partners are carried out regarding the obstacles and problems faced. Furthermore, at the stage of implementing this community service activity, the participants received a presentation on material related to the use of the Foundation's financial submission system and also the provision of a system use module. At the evaluation stage, assistance is carried out on the use of the system after the activity. The expected result of the service activities in the form of this training is to increase the understanding and skills of the Foundation's administrators in terms of using the financial submission application system so that they can optimize the daily operational activities of the Dompet Yatim and Dhuafa Foundations.